An Animal Model for the Implantation of a Bone Liner in the Flexible Implant Arthroplasty - McGehee, J. A.; Swanson, A. B.; Braden, T. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
A retrospective study of silicone elastomer implants used clinically as a flexible implant in the metacarpophalangeal (MP) and proximal interphalangeal (PIP) joints in humans indicated a 7.6% implant fracture failure rate. Implant fractures appeared to occur from tear propagation due to damage resulting from the impingement of the sharp bone edges upon the implant’s surface. A protective synthetic bone liner was devised to reduce in vivo damage and prevent implant failures. The rabbit stifle was used as the animal model for the human metacarpophalangeal and proximal interphalangeal joint and 73 implant arthroplasties were successfully performed.
Keywords: Bone liner; Flexible implant arthroplasty; Silicone elastomer implants; Implant fractures